Are breast milk and serum irisin levels affected by the BMI and nutritional status? A prospective observational study - Yilmaz, Feray cagiran; Turkoglu, Semra; Erman, Fazilet (Springer, 2025)
The influence of maternal nutritional status and anthropometric measurements on breast milk and serum irisin levels remains unclear. This study is the first to explore this relationship. This study aims to investigate the association between maternal BMI and nutritional status in the first month postpartum and their impact on breast milk and serum irisin levels. Forty-five mothers and their infants participated. Anthropometric measurements were taken at one month postpartum, maternal dietary intake was recorded over three days, and breast milk and serum irisin levels were analyzed. Overweight and obese mothers had lower breast milk irisin levels but higher serum irisin levels. A positive correlation was observed between breast milk irisin levels and infant birth weight. Additionally, serum irisin levels were positively associated with infant weight and height at one month. Maternal fiber intake was positively correlated with breast milk irisin levels, whereas fat intake showed a negative correlation. Moreover, higher folate, B12, and zinc intake were linked to increased breast milk and serum irisin levels.Conclusion: Maternal BMI and nutritional status significantly influence breast milk and serum irisin levels. Promoting healthy eating habits and maintaining an optimal body weight before and after pregnancy may enhance irisin levels, potentially supporting infant growth and metabolic health. What is known:center dot Irisin is a myokine involved in energy metabolism and insulin sensitivity, and breast milk composition is influenced by maternal BMI and nutritional status.center dot The effect of maternal obesity on breast milk irisin levels remains insufficiently understood.What is new:center dot This is the first study to evaluate the association between maternal BMI, nutritional status, and both breast milk and serum irisin levels.center dot Overweight and obese mothers exhibit lower breast milk irisin but higher serum irisin levels, and maternal intake of fiber, fat, folate, vitamin B12, and zinc is significantly associated with irisin levels.
Keywords: Irisin; Obesity; BMI; Mothers; Infants